Hiob Miłosza - Szczepan-Wojnarska, Anna M. (Colloquia Litteraria, 2011)
Miłosz’s poetry asks numerous questions concerning an idea of guilt, forgiveness and suffering nevertheless it never provides easy answers, rather multiplies them creating an atmosphere of overwhelming inescapable responsibility. This essay examines the problem of suffering and its implications in relation to figure of biblical Job that appears in Miłosz oeuvre repeatedly and undergoes a kind of the poet’s interpretation in Miłosz’s translation of the Book of Job. The main thesis of my considerations is that various strategies of approaching the problem of suffering applied by Miłosz culminate in the conviction that the Joban deepest pain is his uniqueness, his being incomparable to anyone else. The only faith that can sustain in the context of WWII is “a faith through thankfulness” despite evil that ruled the world at that time.